Learning Process in Teaching and Bio-pedagogical Knowledge Building - Luz Emilia Flores-Davis (Universidad Nacional, Costa Rica, 2012)
Bio-pedagogy is built on praxis, i.e. the interrelationship between reflection and innovative action where these two merge in the construction of senses to generate knowledge. Then, the following question arises: How is teaching understood? How can practice be renovated from the action-reflection-action in a recurring manner and in life itself? A way to search for those answers is the systematization of experiences -a modality of qualitative research. It promotes the transformation of a common practice, based on knowledge building by holistic approaches to the educational process complexity. The systematization of bio-pedagogical experiences involves self-organization, joy, uncertainty and passion; it respects freedom and autonomy, and generates relational spaces, which promote creative processes in learning.